(3GdEWGQ GdOdGdi dJbOje GdCMRGH hGdcJd GdSjGSjI GdeUQjI OGNd GdNWGH GdNHQi HGdUMa GdNGUI (B/ s - (3hSGe eMeO YeQ gfOis; (3TjQjf SdGeI (B: s; (3eMehO Ndjd (B: s ((3GdbGgQI (B: s (3hSGe eMeO YeQ gfOi (B: s, 2014)
(3SYJ gPg GdO QGSI Edi GdcTa Yf GdCWQ GdQFjSjI hGdaQYjI GdJi hXaJgG GdUMa GdNGUI (B{u(32013(B} (3YjfI GdOQGSI(B- (3hGdeJeKdI ai UMa (B" (3GdeUQi Gdjhe(B" (3h(B"(3GdTQhb(B" (3h(B"(3GdJMQjQ(B" (3ai JfGhdgG GdGMRGH hGdMQcGJ hGdcJd GdSjGSjI GdeNJdaI (B: (3hbO GfWdbJ GdO QGSI GdMGdjI ef aQVjI CSGSjI Jbhd Cf GdUMa GdeUQjI GdNGUI JMhdJ Edi UMa eSJbWHI Ch eJMRHI JJHfi QDi hefWdbGJ CMRGH Ch cJd SjGSjI eYjfI ef NdGd NWGHgG GdNHQi (B. (3hbO GSJYGfJ GdOQGSI HCOGI JMdjd Mbhd GdOdGdI HgOa GdJYQa Ydi THcI GdCdaGX hGdeaQOGJ GdOGdI GdJi hXaJgG GdUMa GdNGUI YjfI GdO QGSI YfO JfGhdgG ddCMRGH hGdMQcGJ hGdcJd GdSjGSjI GdeNJdaI (B: (3MjK Je JQLeI GdfUhU GdNHQjI Edi eLehYI ef GdMbhd GdeaghejI (B: (3hGdJi jMJhi cd efgG Ydi THcI ef GdYdGbGJ Hjf GdeaQOGJ HOGNdg(B. s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdUMGaI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCMRGH GdSjGSjIs; (3GdEWGQ GdOdGdi s; (3GdcJd GdSjGSjIs